2015
DOI: 10.1016/j.stemcr.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Use of RUNX2 Expression to Identify Osteogenic Progenitor Cells Derived from Human Embryonic Stem Cells

Abstract: SummaryWe generated a RUNX2-yellow fluorescent protein (YFP) reporter system to study osteogenic development from human embryonic stem cells (hESCs). Our studies demonstrate the fidelity of YFP expression with expression of RUNX2 and other osteogenic genes in hESC-derived osteoprogenitor cells, as well as the osteogenic specificity of YFP signal. In vitro studies confirm that the hESC-derived YFP+ cells have similar osteogenic phenotypes to osteoprogenitor cells generated from bone-marrow mesenchymal stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 29 publications
6
50
0
2
Order By: Relevance
“…The expression of surface markers (CD73, CD90, and CD105), data from gene expression analysis, and Alizarin Red and immunofluorescent staining demonstrate the osteogenic commitment and differentiation potential of these GFP-expressing hESCs. These results are in agreement with previous studies [10, 15, 20, 34, 35]. These data also suggest the stable expression of GFP in hESC-OPs and the genetic manipulation did not affect their osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The expression of surface markers (CD73, CD90, and CD105), data from gene expression analysis, and Alizarin Red and immunofluorescent staining demonstrate the osteogenic commitment and differentiation potential of these GFP-expressing hESCs. These results are in agreement with previous studies [10, 15, 20, 34, 35]. These data also suggest the stable expression of GFP in hESC-OPs and the genetic manipulation did not affect their osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 93%
“…These cell lines effectively report for pluripotency and hence play a role in detection of PSCs from their differentiated progenies. Similarly, Zou et al generated a RUNX2 promoter driven YFP based reporter system in hESCs to track their commitment to osteogenic lineage [15]. Using these transgenic hESCs, they elegantly demonstrated that BMP2 does not induce osteogenic differentiation but promotes the generation of CD73+ osteoprogenitors and their osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is further corroborated by a recent manuscript in which RUNX2 was identified as one of the miR‐1305 targets . RUNX2 is an important osteogenic regulator shown to regulate the length of G1 phase of the cell cycle and apoptosis in highly proliferating mammary epithelial cells . Given that miR‐1305 is also involved in cell cycle regulation and apoptosis in pluripotent stem cells, it would be of interest to further investigate whether these two processes are mediated via regulation of RUNX2 .…”
Section: Discussionmentioning
confidence: 60%
“…This suggests that there is an uncertain threshold above which Mg induces differentiation, either by itself or in the presence of Sr (and minor reduction in Ca). RUNX2 expression typically increases during osteogenic differentiation, 33,34 but can also remain constant. 35 Extract 1 has a significantly increased RUNX2 expression [ Figure 3(B)], confirming signs of differentiation thus complementing the ALPL expression results [ Figure 3(A)].…”
Section: Discussionmentioning
confidence: 99%